Union voices : tactics and tensions in UK organizing - Simms, Melanie (Cornell paperbacks, 2013)
This book evaluates how labor unions fared in the political and institutional context created by Great Britain's New Labour government, which was in power from 1997 to 2010. The book presents a multilevel analysis of what organizing means in the UK, how it emerged, and what its impact has been.